ANALISIS KEBIJAKAN KEWAJIBAN VAKSINASI COVID-19 OLEH PEMERINTAH TERHADAP SETIAP WARGA MASYARAKAT DALAM PERSPEKTIF HAK ASASI MANUSIA DAN HAK KONSTITUSIONAL WARGA NEGARA - Oskar Arifandi Ginting; M. Yamin Lubis; Ibnu Affan (Jurnal Ilmiah METADATA, 2021)
The role of the state in fulfilling the basic needs of the people is very necessary, especially in the form of comprehensive health services, with health being recognized as one of the human rights. The formulation of the problem in this thesis is how to regulate the implementation of vaccination against citizens, what are the factors that cause rejection from the community towards the implementation of vaccination programs organized by the government, whether the obligation to carry out vaccinations against citizens is contrary to human rights and constitutional rights of citizens. This type of research is normative juridical, namely research based on law. Data analysis was carried out qualitatively, which is a form of analysis that does not rely on numbers but on sentences. Drawing conclusions in this paper is carried out using deductive-inductive logic of thinking that is done with the theory that is used as a starting point for conducting research. The results of the study indicate that the regulation of the implementation of vaccination against citizens is regulated in the Indonesian constitution which guarantees health insurance for its citizens, as embodied in Article 28H paragraph (1) of the 1945 Constitution of the Republic of Indonesia. by the government, health workers who have survived Covid-19 still have doubts about being vaccinated, the environment, namely if the people closest to them are against and continue to influence them, there is a possibility that they will also be against the effectiveness of vaccines, mindsets, values ​​held and people doubt the halalness of vaccines. The obligation to carry out vaccination of citizens is a basic right that must be guaranteed, because health is part of the primary needs of every human being and in the perspective of fulfilling the basic rights of citizens to health, the government is bound by the responsibility to ensure adequate access for every citizen to health services that appropriate and optimal as an effort to respect, protect and fulfill state obligations by implementing human rights norms on the right to health.